Systematic study on mix design optimization and on fresh properties of grouts containing crystalline admixtures. - Da Rocha Gomes, Suelen; Santacruz-Cruz, María Isabel; Sánchez, Luis; Sánchez Moreno, Mercedes (Springer Nature, 2025)
Crystalline admixtures (CA) are often proposed as admixtures for improving self-healing ability of cement-based materials. While significant progress has been made in smart concretes and mortars, the application of self-healing technology in grouts remains underexplored. The design of a grout is complex because any change in its composition will have a significant effect on its properties, especially in the fresh state. This work analyses the effect of the incorporation of the CA on the production of a selfrepairing grout. The study focuses on the effects of CA on the fresh and hardened properties of grouts. A comprehensive analysis of grout design highlights the influence of critical parameters such as water/binder (w/b) and sand/binder (s/b) ratios, supplementary materials (fly ash and limestone), and superplasticizer (SP) dosages. Formulating a grout with CA requires greater efforts to achieve an optimal balance between the fresh and hardened properties. CA affected particle dispersion, stability and consistency of grouts. Designing grouts (with and without CA) with similar fluidity required higher SP dosages, which improved the viscosity and delayed the setting time. CA accelerates the hydration of C3S and C3A hydrates formation and shortens the induction period, but when combined with SP, its contribution is reduced. Compressive strength of grout with CA were higher than reference at all tested ages.
Keywords: Lechada; Materiales compuestos; Cemento - Aditivos; Grout; Mix design; Crystalline admixtures; Workability